Acts of Worship for Muslim Women with Vaginal Bleedings from the Islamic Perspective - Basri, Ibrahim; Wan Saifuldin, W.H.; Rahimah, Embong; Syed Hadzrullathfi, Syed Omar (2016)
This study aims to explain the acts of worship (ibadah) for Muslim women who experience vaginal bleeding according to the Islamic perspective. This to make them aware and understand what are the do's and the don't's during the bleeding period. Therefore, it serves as a guideline for the Muslim women when performing various acts of worship while having vaginal bleeding. This study is based on qualitative research method. Data were collected from literature research which involved references on the Quranic exegesis (tafsir), al-Sunnah reviews, authentic books of Islamic jurisprudence 1(fiqhmuktabar) and small booklets. It is found that women with hayd and nifas are not allowed to perform intrinsic ibadah such as taking ablution (wudhu'), performing prayer (salah) and fasting during the month of Ramadhan. They are also not permitted to touch and recite the Qur'an. Meanwhile during pilgrimage (Haj), women with menstruation (haidh) or post-natal bleeding (nifas) may perform the ibadah of Hajj except performing circumambulation (tawaf) and the subsequent two-rakats salah. Some scholars, however, allow woman with haidh or nifas to touch and recite the Quran for teaching purposes as well as to protect its nobility from being tarnished. Meanwhile, for women with vaginal bleeding (istihada), they are permitted to perform all acts of ibadah mentioned above because they are considered to be under ritually pure state.